Correlation of maximum oxygen consumption with component composition of the body, body mass of men with different somatotypes aged 25-35 - Viacheslav M. Miroshnichenko; Yuriy M. Furman; Oleksandra Yu. Brezdeniuk; Victoria E. Onyshchuk; Natalia V. Gavrylova; Svitlana V. Salnykova (IP Iermakov S.S., 2020)
Background and Study Aim: The somatotype determines not only physical development, but also the functional capabilities of the organism. Investigation of the correlation relations between the component of body and VO2 max will reveal the influence of each of the components on the aerobic capacity of men in the first period of mature age. The aim of the work - to detect the peculiarities of manifestation of maximum oxygen consumption of men with different somatotypes and to investigate the relationship with the component composition of the body. Material and Methods: The study involved 150 men aged 25-35 years. The somatotype was determined by the Heath-Carter method. The component composition of the body was determined by the bioelectrical impedance method. The VO2 max indicator was determined, metered loads were performed on a bicycle ergometer. A correlation analysis of the absolute and relative VO2 max values with the fat and muscle components of the body was performed. Results. A high degree of inverse correlation between the relative VO2 max indicator with body mass in men of mesomorphic somatotype was established and a high degree of inverse correlation between the relative VO2 max indicator with body mass and BMI in men of endomorphic-mesomorphic somatotype. Conclusions: For representatives of the mesomorphic and endomorphic-mesomorphic somatotype, a larger body mass and a high degree of correlation between body mass and relative VO2 max indicator are characteristic. For representatives of the ectomorphic and balanced somatotype, a smaller body mass and a lower degree of correlation between body mass and relative VO2 max indicator max are characteristic.